Distributions generated by the boundary values of functions in Privalov spaces - Saliji, Mejdin; Bedjeti, Bedrije; Manova Erakovikj, Vesna (JOURNAL OF ADVANCES IN MATHEMATICS, 2022)
We characterise the distributions generated by the boundary values of functions from Privalov spaces.